EFFECT OF YOGA AND ACUPRESSURE ON PAIN AND FUNCTIONAL CAPABILITY OF LOWER BACK IN PREGNANT MOTHERS DURING THE THIRD TRIMESTER OF PREGNANCY - Dewi Candra Resmi; Suharyo Hadisaputro; Runjati Runjati (Belitung Nursing Journal, 2017)
Objective: To examine the effect of yoga and acupressure in lower back pain and functional capability in pregnant women during the third semester of pregnancy. Methods: A quasi-experimental design with pretest posttest with non-equivalent control group. The research was conducted at the Community Health Center of Kalikajar I, Selomerto I and Garung I in Wonosobo regency Indonesia in January 2017. The samples of this research were 42 pregnant women in trimester III selected using purposive sampling, which 14 samples assigned in the yoga group, acupressure group, and control group. A Visual Analog Scale (VAS) was used to measure pain level, and Oswestry Disability Index to measure functional capability of lower back. Data were analyzed using paired t-test and one-way ANOVA. Results: Findings showed that there was a statistically significant effect of yoga, acupressure, and pregnancy exercise (control group) in reducing lower back pain and lower back functional capability with p <0.05. Pregnancy exercise (mean=-1.43) was more effective in reducing lower back pain compared with yoga (mean=-2.29) and acupressure (mean=-2.71); and acupressure (mean=-14.29) was more effective in improving lower back functional capability than yoga (mean=-6.57) and pregnancy exercise (mean= -13.29). Conclusion: There were significant effects of yoga, acupressure, and pregnancy exercise in reducing pain and in improving the functional ability of the lower back. It is recommended for midwife to use these interventions as an alternative to deal with back pain and functional capability in pregnant women, especially in the Community Health Center in Wonosobo regency, Indonesia.